Global leadership for a reputable university - Hassanzadeh, Maryam; Silong, Abu Daud (Universiti Putra Malaysia Press, 2015)
In Malaysia the concept of a reputable university is very hotly debated. It was a hot issue when an opposition Member of Parliament mentioned that Malaysian universities are not ranked among the top 100 world universities. Some of our premier universities did poorly in the ranking. One of the key factors of transforming Malaysian universities into reputable universities is leadership. In the context of globalization, Malaysian universities need leaders who can work on a global stage. This study attempts to understand the concept of global leadership, which is important for leading a university of international repute. This research employed qualitative means, utilizing the in-depth interview for data collection. Data were collected from eight past and present top leaders of a university in Malaysia. The data collected from the interviews were then transcribed verbatim, coded, analyzed, interpreted and discussed accordingly. There are various factors that will enable our universities to become internationally reputable universities. Among others are abundance of resources, quality academicians, quality students and good governance. Based on the findings of the study, one of the key factors of transforming our universities into reputable universities is leadership. In the context of the new environment, we need leaders who can become global players.